INDICATORS OF FOREIGN POLICY EFFICIENCY RESEARCH IN THE POLITICAL-DIPLOMATIC FIELD (World Bulletin of Management and Law, 2023)
The article analyzes a group of indicators in the political-diplomatic field for researching the effectiveness of foreign policy. Also, the relevance and importance of these indicators are scientifically and practically justified with the help of examples.
Keywords: indicator; mediator; sanction; sovereignty